On the issue of loci communes in folklore studies - Okay, A.; Zhumabekov, M.K.; Demyanova, Yu.A. (KSU Publ., 2017)
Modern folkloristics as an independent science solves a number of important problems: comprehends its subject, creates its own theory, and develops folklore research methods. The area of poetic style in folklore is essentially important among the specified problems. It covers various aspects of structural and figurative organization and artistic expressiveness of folkloreworks. The complexity of a research of these questions comes from the need of their consideration at the different levels of folklore poetry: mental (as an expression of national consciousness), verbal (as the component of the verbal text) and functional (as the method of performing practice). We do not claim to give inclusive solution of the problem; in this article the subject of our research is one of particular manifestations of folklore art style – loci communes or so-called «typicality» representing the poetic device which is the most widespread in the world folklore.
Фольклор туралы ғылымдағы «loci communes» мəселелері
К вопросу «loci communes» в науке о фольклоре
Keywords: folklore; loci communes; ceremony; metacode; genesis; semantics; typicality; animism; anthropomorphism; symbolism; methodology of folklore research